Symmetric Dimethylarginine for Risk Stratification of Cardioembolic Stroke - Johanna Ernst; Ilai Mick Albert Darius Kaulbarsch; Svenja L. Jochmann; Maria M. Gabriel; Ramona Schuppner; Ralf Lichtinghagen; Jens Martens-Lobenhoffer; Hannelore Ehrenreich; Stefanie M. Bode-Böger; Anika Grosshennig; Karin Weissenborn; Rieke Ringlstetter; et al. (Translational Stroke Research, 2026)
A significant proportion of ischemic strokes are classified as embolic stroke of undetermined source (ESUS), complicating secondary prevention. Nitric oxide metabolism is regulated by L-arginine (Arg), asymmetric (ADMA) and symmetric dimethylarginine (SDMA), contributing to increased cardiovascular risk. Previous studies suggest that SDMA and the ratio of Arg/SDMA help to detect atrial fibrillation (AF). We hypothesized that SDMA and Arg/SDMA improve diagnosis of cardioembolic stroke (CES), which may enable more accurate secondary prevention. This prospective nested case-control study included ischemic stroke patients (CES or ESUS) at Hannover Medical School between January 2022 and July 2023. Blood samples were collected after 24 h of stroke onset. ADMA, SDMA and Arg concentrations were measured and relevant biomarker ratios were calculated. Logistic regression and receiver operating curve analyses examined discriminatory biomarker performances for CES versus ESUS, alongside established clinical risk scores. 235 patients (107 CES, 128 ESUS) were analyzed. Arg/SDMA ratio and SDMA values showed comparable or better discriminatory power between CES and ESUS than clinical AF scores (AUC SDMA = 0.71 (95%CI: 0.64–0.77, p < 0.001); AUC Arg/SDMA = 0.74 (95%CI: 0.67–0.80, p < 0.001)). The same was true for AF detected after stroke (AFDAS) vs. ESUS. When combining Arg/SDMA-ratio and AS5F, the diagnostic accuracy was modestly improved compared to AS5F alone (DeltaAUC = 0.03 (95%CI: -0.06-0.11)). In conclusion, SDMA and Arg/SDMA ratio can serve as biomarkers for AF and AFDAS. While the additional predictive value in combination with clinical scores may be limited, these findings support the pathogenic role of the Arg/SDMA pathway in stroke pathophysiology. Trial Registration : The study is retrospectively registered in the German Clinical Trial Register (StudyID DRKS00038459).

Idiopathic spontaneous intracardiac microbubbles in an adult dog - L. Beeby; M. Martinez; E.F. Bode (Journal of Veterinary Cardiology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Dispersal patterns of sandfish (Holothuria scabra) larvae in Manus Province, Papua New Guinea - Peter Waldie; David A. Feary; Michael Bode; Manuai Matawai; Hugo B. Harrison; Michael L. Berumen; Chris Molai; Maunoa Karo; Richard J. Hamilton (Frontiers in Marine Science, 2024)
In many tropical nations, coastal communities seek to manage their sea cucumber fisheries by establishing locally managed marine areas on their traditional fishing grounds. These managed areas can protect spawning stocks, however the extent to which they help to replenish nearby sea cucumber fisheries is debated, as nothing is known about the scales at which sea cucumber larvae disperse. In this study, we used genetic parentage analyses and statistical modelling to provide the first empirical measure of larval dispersal patterns for a sea cucumber species. We analysed tissue samples from 765 adult and 827 juvenile sandfish ( Holothuria scabra ) collected from five traditional fishing grounds of the Titan tribe, from Manus Province, Papua New Guinea. All adults were sampled from the Pere fishing grounds (the larval source area), with juveniles sampled from the Pere, Mbunai, Tawi, Timonai and Mbuke fishing grounds. Parentage analysis identified 15 juveniles that were the offspring of parents sampled from Pere fishing grounds, with six of these juveniles located in the same fishing grounds as their parents. The best-fit larval dispersal kernel predicted that the average H. scabra larvae travelled 15 km from its spawning location, with 50% of larvae settling within 6.7 km of their parents and 95% of larvae settling within 59 km of their parents. These results suggest that the Titan tribes’ desire to protect their H. scabra spawning stocks by establishing a network of locally managed marine areas across 65 km of continuous coastline is a culturally appropriate strategy, which has merit from both an ecological and fisheries standpoint.

The Need to Prioritize People With Disabilities in Nutrition Education - Kelseanna Hollis-Hansen; Jody Vogelzang; Bree Bode; Adrienne Markworth; Rebecca L. Rivera; Nazanin Heydarian; Rebecca Russell; Emily Watt Clarke (Journal of Nutrition Education and Behavior, 2024)

Macronutrients and Metabolizable Energy: Preliminary Findings from a Global Study to Characterize Nutrients in Donor Human Milk - M. Perrin; K. Mansen; K. Israel-Ballard; L. Bode (Journal of the Academy of Nutrition and Dietetics, 2023)

Comparative pathology of VIC01 isolate and Omicron variant of SARS-CoV-2 infection, including a rechallenge model, in the Golden Syrian hamster - E. Rayner; K. Ryan; Y. Hall; L. Hunter; C. Kennard; J. Edun Hughes; J. Salguero Bodes (Journal of Comparative Pathology, 2023)

Green and sustainable solvents for biocatalytic oxidations - Roger A. Sheldon; Moira L. Bode; Nompumelelo Mathebula (Current Opinion in Green and Sustainable Chemistry, 2023)

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

Correction to: Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Ocean zoning within a sparing versus sharing framework - Jennifer McGowan; Michael Bode; Matthew H. Holden; Katrina Davis; Nils C. Krueck; Maria Beger; Katherine L. Yates; Hugh P. Possingham (Theoretical Ecology, 2018)

Minimizing species extinctions through strategic planning for conservation fencing - Jeremy L. Ringma; Brendan Wintle; Richard A. Fuller; Diana Fisher; Michael Bode (Conservation Biology, 2017)
Conservation fences are an increasingly common management action, particularly for species threatened by invasive predators. However, unlike many conservation actions, fence networks are expanding in an unsystematic manner, generally as a reaction to local funding opportunities or threats. We conducted a gap analysis of Australia's large predator‐exclusion fence network by examining translocation of Australian mammals relative to their extinction risk. To address gaps identified in species representation, we devised a systematic prioritization method for expanding the conservation fence network that explicitly incorporated population viability analysis and minimized expected species’ extinctions. The approach was applied to New South Wales, Australia, where the state government intends to expand the existing conservation fence network. Existing protection of species in fenced areas was highly uneven; 67% of predator‐sensitive species were unrepresented in the fence network. Our systematic prioritization yielded substantial efficiencies in that it reduced expected number of species extinctions up to 17 times more effectively than ad hoc approaches. The outcome illustrates the importance of governance in coordinating management action when multiple projects have similar objectives and rely on systematic methods rather than expanding networks opportunistically.

Reef-fish larval dispersal patterns validate no-take marine reserve network connectivity that links human communities - Rene A. Abesamis; Pablo Saenz-Agudelo; Michael L. Berumen; Michael Bode; Claro Renato L. Jadloc; Leilani A. Solera; Cesar L. Villanoy; Lawrence Patrick C. Bernardo; Angel C. Alcala; Garry R. Russ (Coral Reefs, 2017)

Large‐scale, multidirectional larval connectivity among coral reef fish populations in the Great Barrier Reef Marine Park - David H. Williamson; Hugo B. Harrison; Glenn R. Almany; Michael L. Berumen; Michael Bode; Mary C. Bonin; Severine Choukroun; Peter J. Doherty; Ashley J. Frisch; Pablo Saenz‐Agudelo; Geoffrey P. Jones (Molecular Ecology, 2016)
Larval dispersal is the key process by which populations of most marine fishes and invertebrates are connected and replenished. Advances in larval tagging and genetics have enhanced our capacity to track larval dispersal, assess scales of population connectivity, and quantify larval exchange among no‐take marine reserves and fished areas. Recent studies have found that reserves can be a significant source of recruits for populations up to 40 km away, but the scale and direction of larval connectivity across larger seascapes remain unknown. Here, we apply genetic parentage analysis to investigate larval dispersal patterns for two exploited coral reef groupers ( Plectropomus maculatus and Plectropomus leopardus ) within and among three clusters of reefs separated by 60–220 km within the Great Barrier Reef Marine Park, Australia. A total of 69 juvenile P. maculatus and 17 juvenile P. leopardus (representing 6% and 9% of the total juveniles sampled, respectively) were genetically assigned to parent individuals on reefs within the study area. We identified both short‐distance larval dispersal within regions (200 m to 50 km) and long‐distance, multidirectional dispersal of up to ~250 km among regions. Dispersal strength declined significantly with distance, with best‐fit dispersal kernels estimating median dispersal distances of ~110 km for P. maculatus and ~190 km for P. leopardus . Larval exchange among reefs demonstrates that established reserves form a highly connected network and contribute larvae for the replenishment of fished reefs at multiple spatial scales. Our findings highlight the potential for long‐distance dispersal in an important group of reef fishes, and provide further evidence that effectively protected reserves can yield recruitment and sustainability benefits for exploited fish populations.

A systematic review and meta-analysis on Staphylococcus aureus carriage in psoriasis, acne and rosacea - J. E. E. Totté; W. T. van der Feltz; L. G. M. Bode; A. van Belkum; E. J. van Zuuren; S. G. M. A. Pasmans (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Heterogeneity of the humoral immune response following Staphylococcus aureus bacteremia - N. J. Verkaik; H. A. Boelens; C. P. de Vogel; M. Tavakol; L. G. M. Bode; H. A. Verbrugh; A. van Belkum; W. J. B. van Wamel (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Piperacillin-tazobactam in pediatric cancer patients younger than 25 months: a retrospective multicenter survey - A. Simon; T. Lehrnbecher; U. Bode; A. H. Groll; L. Tramsen; R. Wieland; E. Molitor; G. Fleischhack; H. J. Laws (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

No evidence of endemic Borna disease virus infection in Australian horses in contrast with endemic infection in other continents - S. Kamhieh; J. Hodgson; L. Bode; H. Ludwig; C. Ward; R. L. P. Flower (Archives of Virology, 2006)

Effects of ENU dosage on mouse strains - Monica J. Justice; Don A. Carpenter; Jack Favor; Angelika Neuhauser-Klaus; Martin Hrabé de Angelis; Dian Soewarto; Amy Moser; Sabine Cordes; Darla Miller; Verne Chapman; John S. Weber; Eugene M. Rinchik; et al. (Mammalian Genome, 2000)

Presence of antibodies reacting with porcine circovirus in sera of humans, mice, and cattle - I. Tischer; L. Bode; J. Apodaca; H. Timm; D. Peters; R. Rasch; S. Pociuli; E. Gerike (Archives of Virology, 1995)

Distribution of antibodies to porcine circovirus in swine populations of different breeding farms - I. Tischer; L. Bode; D. Peters; S. Pociuli; B. Germann (Archives of Virology, 1995)